Aluminum cluster for CO and O-2 adsorption - Samanta, Bipasa; Sengupta, Turbasu; Pal, Sourav (Journal of Molecular Modeling, 2019)
Low temperature oxidation of CO to CO2 is an important process for the environment. Similarly adsorption of CO from the releasing sources is also of major concern today. Whereas the potential of gold and silver clusters is well proven for thecatalysis of the above mentioned reaction, the potential of aluminum (Al) clusters remains unexplored. The present study proves that, similar to the transition metals, Al clusters can also be used for adsorption of gases. We first tested the potential of Al cluster as adsorbents for CO. The high binding energy (BE) values prove that Al clusters can be used for adsorbing both CO and O-2. Since oxygen binding is more facile, we adsorbed oxygen on Al and then checked the effect of this O-2 on the BE of CO. The results were obtained by DFT calculations at M062X/TZVP level of theory.
Keywords: Aluminum clusters; Charge decomposition analysis; CO adsorption; DFT; O-2 adsorption; Wiberg bond indices